2016
DOI: 10.1159/000445125
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LDHA Deliver Potential Anticancer Performance in Renal Cell Carcinoma

Abstract: Purpose: Lactate dehydrogenase A (LDHA), which functions as a crucial enzyme in transforming from pyruvate into lactate, has been reported to be overexpressed in various advanced cancer and its silencing has turned out to be tumor suppressive. Previous studies have showed that the expression of LDHA was higher in renal cell carcinoma (RCC) than that in corresponding normal renal tissue. However, the function of LDHA in RCC, and its possible mechanism in tumor progression, has not been investigated. Methods: MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…LDHA catalyzes the conversion of pyruvate to lactate and is considered to be a key checkpoint of anaerobic glycolysis (9). Increased levels of LDHA have been reported in several types of tumors (11,(13)(14)(15), and its expression levels have been correlated with clinical stages in breast cancer, renal cell carcinoma and prostate cancer; these reports further support that therapies targeting LDHA may provide useful strategies for controlling cancer progression. Moreover, previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to those in matched normal tissues; these results prompted us to determine the correlation between LDHA expression levels and glioma malignancy (16).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…LDHA catalyzes the conversion of pyruvate to lactate and is considered to be a key checkpoint of anaerobic glycolysis (9). Increased levels of LDHA have been reported in several types of tumors (11,(13)(14)(15), and its expression levels have been correlated with clinical stages in breast cancer, renal cell carcinoma and prostate cancer; these reports further support that therapies targeting LDHA may provide useful strategies for controlling cancer progression. Moreover, previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to those in matched normal tissues; these results prompted us to determine the correlation between LDHA expression levels and glioma malignancy (16).…”
Section: Discussionmentioning
confidence: 83%
“…In pancreatic cancer, when LDHA was overexpressed, tumor growth was increased (13). In renal cell carcinoma, knocking down LDHA resulted in potential anticancer effects (14). Although the abnormal expression of LDHA has been reported in several cancers (10)(11)(12)(13)(14)(15), little is known about the expression pattern of LDHA and its underlying roles in GBM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental knockdown of LDHA in diverse malignant cell types has been reported to reduce glycolytic activity (5, 6), attenuate extruded lactate and ATP, tantamount to hampered cell proliferation, migration, invasion (710) and radio sensitization (11). Further, a number of studies are showing LDHA mRNA as being degraded by miRNAs: miR34a, miR-34c, miR-369-3p, miR-374a, and miR-4524a/b where overexpression of some of these can prevent resistance to radiation (8, 12) and chemotherapeutic drugs (13, 14).…”
mentioning
confidence: 99%